ANALISIS KETEBALAN ENDAPAN LATERIT DAN PENGARUHNYA TERHADAP KADAR NIKEL DI DAERAH KONINIS, KABUPATEN BANGGAI - Nonsi, Mutiara; Arifin, Yayu Indriati; Akase, Noviar (UNM Geographic Journal, 2024)
The Koninis region has diverse morphological features accompanied by the formation of nickel laterite deposits, leading to variations in the thickness of these deposits. The research location is administratively part of Banggai Regency, at coordinates 05°0'10" S and 122°15'40" E, within the concession area of PT. Koninis Fajar Mineral, covering approximately 138 hectares. This study aims to understand the morphological conditions and analyze the correlation between the thickness of nickel laterite deposits and the existing morphological conditions in the research area using methods such as geological mapping, petrographic analysis to determine the lithology of the research area, X-Ray Fluorescence (XRF) geochemical analysis to identify the nickel laterite ore zones, and studio analysis. The results indicate a range of laterite thicknesses, from a minimum of 6.5 meters to a maximum of 34 meters, with varying thicknesses within each zone. Analysis shows that thicker saprolite corresponds to higher nickel content, while thicker limonite correlates with lower nickel content.